Provision of service and training for small bowel endoscopy in the UK. Issue 2 (12th December 2011) - McAlindon, Mark E; Parker, Clare E; Hendy, Philip; Mosea, Haider; Panter, Simon; Davison, Carolyn; Fraser, Chris; Despott, Edward J; Sidhu, Reena; Sanders, David S; Makins, Richard
Abstract : Objective: To determine the location and use of small bowel endoscopy services in the UK and to analyse training uptake to assess future demand and shape discussions about training and service delivery. Design: Surveys of British Society of Gastroenterology (BSG) members by web-based and personal contact were conducted to ascertain capsule endoscopy practice and numbers of procedures performed. This was compared with expected numbers of procedures calculated using BSG guidelines, hospital episode statistics and published data of capsule endoscopy in routine practice. Analysis of data from two national training courses provided information about training. Results: 45% of UK gastroenterology services offered in-house capsule endoscopy. 91.3% of survey responders referred patients for capsule endoscopy; 67.7% felt that local availability would increase referrals. Suspected small bowel bleeding and Crohn's disease were considered appropriate indications by the majority. Demand is increasing in spite of restricted use in 21.6% of centres. Only two regions performed more than the minimum estimate of need of 45 procedures per 250 000 population. Eight centres perform regular device-assisted enteroscopy; 14 services are in development. 74% of trainees were interested in training and of those training in image interpretation, 67% are doctors and 28% are nurses. Conclusions: Capsule endoscopy is used by the majority of UK gastroenterologists but appears to be underused. Current demand for device-assisted enteroscopy seems likely to be matched if new services become established. Future demand is likely to increase, however, suggesting the need to formalise training and accreditation for both doctors and nurses.